The Physics of Atoms and Quanta Introduction to Experiments and Theory - Haken, Hermann; Wolf, Hans Christoph (Advanced Texts in Physics, 2005)
The Physics of Atoms and Quanta is a thorough introduction to experiments and theory in this field. Every classical and modern aspect is included and discussed in detail. The new edition is completely revised, new sections on atoms in strong electric fields and high magnetic fields complete the comprehensive coverage of all topics related to atoms and quanta. All new developments, such as new experiments on quantum entanglement, the quantum computer, quantum information, the Einstein-Podolsky-Rosen paradoxon, Bell's inequality, Schrödinger's cat, decoherence, Bose-Einstein-Condensation and the atom laser are discussed. Over 170 problems and their solutions help deepen the insight in this subject area and make this book a real study text. The second and more advanced book by the same authors entitled "Molecular Physics and Elements of Quantum Chemistry" is the completion of this unique textbook.